An efficient fine-grained access control scheme for hierarchical wireless sensor networks. (2018) - Chatterjee, Santanu; Roy, Sandip; Chattopadhyay, Samiran
Fine-grained access control is used to assign unique access privilege to a particular user for accessing real-time data directly from the nodes inside wireless sensor network (WSNs). In this paper, we propose a new fine-grained access control scheme based on key policy attribute based encryption (KP-ABE) suitable for hierarchical WSNs. The protocol provides fine-grained access control with authentication along with efficient user revocation and new node deployment policy. Instead of being quite lightweight in nature, the scheme resists many active and passive security attacks. For formal authentication proof and simulation we use BAN logic and widely accepted AVISPA model checkers respectively.